Explain how do you do it If you put only the answer i will report you
![Explain how do you do it If you put only the answer i will report you class=](https://us-static.z-dn.net/files/dd4/81dda7c6d72fe4f4f20cc1fe74238b18.jpg)
![Explain how do you do it If you put only the answer i will report you class=](https://us-static.z-dn.net/files/d0f/cd4085496ddbdfde3463d13a6f4ca56f.jpg)
Answer:
[tex] d = \sqrt{113} = 10.63014 [/tex]
Step-by-step explanation:
Distance between the endpoints of the graph, (-3, 3) and (5, -4), can be calculated using distance formula, [tex] d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} [/tex].
Where,
[tex] (-3, 3) = (x_1, y_1) [/tex]
[tex] (5, -4) = (x_2, y_2) [/tex]
Thus,
[tex] d = \sqrt{(5 - (-3))^2 + (-4 - 3)^2} [/tex]
[tex] d = \sqrt{(8)^2 + (-7)^2} [/tex]
[tex] d = \sqrt{64 + 49} = \sqrt{113} [/tex]
[tex] d = \sqrt{113} = 10.63014 [/tex]